2008
DOI: 10.1515/bmt.2008.022
|View full text |Cite
|
Sign up to set email alerts
|

A novel transcutaneous vagus nerve stimulation leads to brainstem and cerebral activations measured by functional MRI / Funktionelle Magnetresonanztomographie zeigt Aktivierungen des Hirnstamms und weiterer zerebraler Strukturen unter transkutaner Vagusnervstimulation

Abstract: The method and device are feasible and appropriate for accessing cerebral vagus nerve structures, respectively. As functional patterns share features with fMRI BOLD, the effects previously studied with the NCP are discussed and new possibilities of tVNS are hypothesised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(139 citation statements)
references
References 27 publications
2
118
0
3
Order By: Relevance
“…Following the suggestions by Dietrich et al (2008) for optimal stimulation, the tVNS s device was programmed to a stimulus intensity at .5 mA, delivered with a pulse width of 200-300 ms at 25 Hz. Stimulation was active for 30 seconds, followed by a break of 30 seconds.…”
Section: Tvnsmentioning
confidence: 99%
“…Following the suggestions by Dietrich et al (2008) for optimal stimulation, the tVNS s device was programmed to a stimulus intensity at .5 mA, delivered with a pulse width of 200-300 ms at 25 Hz. Stimulation was active for 30 seconds, followed by a break of 30 seconds.…”
Section: Tvnsmentioning
confidence: 99%
“…While Kraus et al [35] and Dietrich et al [11] reported deactivation of the amygdala and accumbens, respectively, using ear stimulation, they did not apply the stimulation to the cymba conchae; regional differential innervation of the ear may account for these different findings.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study in rats provided further evidence of a direct projection of the ABVN to the NTS [19]. Three functional MRI (fMRI) studies in humans investigating the effects of transcutaneous vagus nerve stimulation (t-VNS) via the external ear did not report activation of the NTS, possibly because of methodological differences or because different regions of the external ear other than the cymba conchae were stimulated and were not supplied or insufficiently supplied by the ABVN [11,35,36]. However, the brain regions that were significantly affected by the stimulation in those studies are consistent with primary and higher-order central projections of the vagus nerve.…”
Section: Introductionmentioning
confidence: 99%
“…A transcutaneous method of VNS (t-VNS) targets the cutaneous receptive field of the ABVN. Applying an electrical stimulus to the left cymba conchae (using a stimulus intensity above the sensory detection threshold, but below the pain threshold) results in a brain activation pattern not dissimilar to that of left cervical VNS [16-18]. The use of t-VNS for treating epilepsy was first proposed in 2000 [19].…”
Section: Methods Of Vagus Nerve Stimulationmentioning
confidence: 99%